Microscopic fungi – wall coating destructors of attraction architecture in Kyiv - Домбровська, І. В.; Малиновська, І. М. (Problems of Environmental Biotechnology, 2013)
Mycological analysis was carried out damaged sections of wall covering interior space of the church of St. Nicholas in Kyiv. We found 15 species of mitosporic fungi, 1 specia zygomycetes and 1 specia ascomycetes in an amount of 102-104 CFU/g to 103-107 CFU/g. The degree of damage depended on the number of groups fungi and their representation.